Formation of mouse erythrocyte rosettes by human lymphocytes. A B-cell marker - Dobozy, A. (1976)
26·5±8·6% of human peripheral lymphocytes form rosettes with mouse erythrocytes. There is a significant correlation between the numbers of mouse erythrocyte rosette-forming (MERF) lymphocytes and immunoglobulin-bearing cells. By density gradient centrifugation the MERF cells can be separated from the other lymphocytes. Studies on the isolated MERF cells indicate that every MERF lymphocyte is an Ig-bearing cell, but they do not possess sheep erythrocyte-binding receptors and cannot be stimulated with phytohaemagglutinin. Accordingly, the MERF lymphocytes are regarded as B cells.